Comparison of the morphological characteristics of trichuris eggs from humans (homo sapiens), macaques (macaca fascicularis philippinensis), dogs (canis familiaris) and deers (Cervus mariannus) in New Israel, Makilala, Cotabato - Cubero, Christine Marie Bacatan (2008)
A study was conducted in identity, characterize and compare the morphology of the eggs of Trichuris species from humans (Homo sapiens), macaques (Macaca fascicularis philippinensis), dogs (canis familiaris) and deers (cervus mariannus ) in New Israel, Makilala, Cotabato based on length, width, shape and color. Ninety-nine fecal samples were examined, 51 humans between 4 to 74 years old), 39 macaques (between 10 to 20 years old). 5 dogs (unknown ages) and 4 deers (unknownages) were collected and processed by double centrifiguration fecal flotation technique in saturated sugar solution. A total of 199 trichuris eggs from the four species (18 humans, 80 macaques, 97 dogs and 4 deers) were identified and characterized. Results showed the following mean measurements: 52.8 m by 22.6 m in humans; 55.1 m by 23.7 m in macaques; 73.5 m by 32.8 m in dogs and 53.8 m by 23 m in deers. Dogs, however have longer and wider Trichuris eggs compared to the morphologically similar Trichuris eggs from humans, macaques and deers. Values observed from Trichuris eggs of seven dogs showed a lower measurement (54 m by 23 m) which is similar to those of humans, macaques and deers. Trichuris eggs of eight macaques, however showed higher measurements (72 to 76 m by 32 to 34 m) than values reported by previous literatures which are similar to those of dogs. Shape of Trichuris eggs from humans, macques, and deers have generally lack prominence of plugs except from dogs. Trivhuris eggs from humans, macaques, and deers are usually lighter in color compared to dogs. Other parasites were also noted such as Ascaris spp., Entamoeba spp. And other unidentified parasites.